Backbone-modified oligonucleotides for tuning the cellular uptake behaviour of spherical nucleic acids. (30th January 2017) - Song, Woo Chul; Kim, Kyoung-Ran; Park, Miri; Lee, Kyung Eun; Ahn, Dae-Ro
Abstract : Spherical nucleic acids (SNAs) were prepared using sugar backbone-modified oligonucleotides, and the effects of the oligonucleotides on the cellular uptake efficiency of SNAs were investigated. Abstract : Spherical nucleic acids (SNAs) are spherically arranged oligonucleotides on core inorganic nanoparticles and have great potential for intracellular delivery of bioactive molecules, since they have been found to be internalized into mammalian cells. Understanding the factors that influence the cellular uptake of SNAs would be beneficial to design SNAs with novel uptake properties. We here report the effect of the sugar backbone type of the oligonucleotides on the cellular internalization of SNAs. After the preparation of SNAs with the oligonucleotides of five different sugar backbones, we analyze the cellular uptake efficiency quantitatively by flow cytometry and inductively coupled plasma mass spectrometry (ICP-MS). The data reveal that the uptake efficiencies and the uptake mechanisms significantly rely on the backbone type. These results suggest that the backbone modification can provide a unique handle to tune the cellular uptake behavior of SNAs.